Analysis Of Determining The Selling Price Of Lavender Residence Housing Using The Full Costing Method (Case Study At PT. Cipta Permata Karya Sukses) - Izmi Noviyanti; Puji Isyanto; Neni Sumarni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to determine the difference in selling prices between the target costing method carried out by the company and the full costing carried out by researchers at Lavender Residence housing. This study uses qualitative data with data sources received from housing developers. Data collection techniques were carried out by means of interviews, observations, literature studies and documentation in the form of photos and videos. Data analysis by using descriptive analysis method. The results showed that there were several factors in determining the selling price, namely the high price of land and a significant increase in interest rates. In using the full costing method to produce greater profits that is equal to 15%, the company can get the maximum profit when using this method. However, this method cannot be accepted and used by the company because the company is only focused on sales targets so it will continue to use the target costing method as it has done. Keywords: Selling Price, Full Costing Method, Target Costing Method